2007
DOI: 10.1007/s00467-006-0213-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal vitamin A status on kidney development: a pilot study

Abstract: Nephron endowment ranges widely in normal human populations. Recent autopsy studies have drawn attention to the possibility that subtle congenital nephron deficits may be associated with increased risk of developing hypertension later in life. Since modest maternal vitamin A deficiency reduces nephron number in rats, we designed a pilot study to determine the prevalence of maternal vitamin A deficiency in Montreal (Canada) and Bangalore (India) and the usefulness of newborn renal volume as a surrogate for neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 19 publications
2
45
0
2
Order By: Relevance
“…In humans, maternal protein and micronutrient deficiencies are common in developing countries, and maternal malnutrition, underweight, iron deficiency and anemia are all recognized risk factors for LBW 35 . Vitamin A deficiency is also highly prevalent among pregnant women world-wide ( Figure 2 (Table 1) 38 .…”
Section: Developmental Determinants Of Low Nephron Numbermentioning
confidence: 99%
“…In humans, maternal protein and micronutrient deficiencies are common in developing countries, and maternal malnutrition, underweight, iron deficiency and anemia are all recognized risk factors for LBW 35 . Vitamin A deficiency is also highly prevalent among pregnant women world-wide ( Figure 2 (Table 1) 38 .…”
Section: Developmental Determinants Of Low Nephron Numbermentioning
confidence: 99%
“…122 Vitamin A is an important regulator of cell proliferation and differentiation and plays a critical role in the determination of nephron mass. [123][124][125] Vitamin A deficiency is also common in premature infants 126 due in part to increased urinary losses of vitamin A. 127 Although vitamin A supplementation appears to be beneficial in the lung, another branching organ that develops in late gestation, in protecting against chronic lung disease, 128 there are no clinical data on renal outcomes in humans.…”
Section: Research Horizons Nephrogenesismentioning
confidence: 99%
“…Vitamin A and its derivatives play a vital role in the development and homeostasis of almost every organ of the body by regulating embryogenesis, including kidney development, cell differentiation, proliferation, apoptosis, immune regulation, and metabolism [1][2][3]. Recent studies have revealed that vitamin A also has an effect on energy metabolism, adipocyte differentiation, and lipid metabolism [4][5][6].…”
Section: Introductionmentioning
confidence: 98%